A 12-year record of intertidal barnacle recruitment in Atlantic Canada (2005–2016): relationships with sea surface temperature and phytoplankton abundance - Ricardo A. Scrosati; Julius A. Ellrich (PeerJ, 2016)
On the Gulf of St. Lawrence coast of Nova Scotia (Canada), recruitment of the barnacle Semibalanus balanoides occurs in May and June. Every year in June between 2005 and 2016, we recorded recruit density for this barnacle at the same wave-exposed rocky intertidal location on this coast. During these 12 years, mean recruit density was lowest in 2015 (198 recruits dm−2) and highest in 2007 (969 recruits dm−2). The highest recruit density observed in a single quadrat was 1,457 recruits dm−2 (in 2011) and the lowest was 34 recruits dm−2 (in 2015). Most barnacle recruits appear during May, which suggests that most pelagic larvae (which develop over 5–6 weeks before benthic settlement) are in the water column in April. An AICc-based model selection approach identified sea surface temperature (SST) in April and the abundance of phytoplankton (food for barnacle larvae, measured as chlorophyll-a concentration –Chl-a–) in April as good explanatory variables. Together, April SST and April Chl-a explained 51% of the observed interannual variation in recruit density, with an overall positive influence. April SST was positively related to March–April air temperature (AT). April Chl-a was negatively related to the April ratio between the number of days with onshore winds (which blow from phytoplankton-limited offshore waters) and the number of days with alongshore winds (phytoplankton is more abundant on coastal waters). Therefore, this study suggests that climatic processes affecting April SST and April Chl-a indirectly influence intertidal barnacle recruitment by influencing larval performance.